(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
The purpose of this thesis is to implement a new method of teaching called “Knowledge – Practice, Analyze – Practice (KPAP)” in an auditory of high education. This method can solve several previous problems in classical teaching system as well as it can also open the special door for both teachers and students to have teacher-student-friendly atmosphere. This method can be used for mainly practical means of subjects related to mostly in practical atmospheres of teaching. This method consists of two main stages to be taken to achieve the best practical experience so far. This method may seem to be the same as seminar lessons which have been conducted in many high schools and institutions. However, this is completely different with the old method of teaching as I will explain it below